Polarization properties of a fiber optic loop mirror. (August 2021) - Armas-Rivera, I.; Rodriguez-Morales, L.A.; Beltrán-Pérez, G.; Durán-Sánchez, M.; Andrés, M.V.; Ibarra-Escamilla, B.
Highlights: The polarization properties of the reflection strongly depends on the angle rotation. With proper parameters, the polarization is constant for any modulation depth. The modulation depth can be controlled by angle rotation. The polarization of the transmission is always orthogonal to the input. Abstract: In this work, we present the spectral polarization properties of a fiber optic loop mirror (FOLM) which includes a 50/50 coupler and 25-cm long highly birefringent (hi-bi) fiber. The modulation depth of the reflection/transmission spectra can be adjusted by twisting the hi-bi fiber at the splices by means of two azimuth rotators (AR). The results show that the polarization properties of the reflection strongly depends on the angle rotation. We found that it is possible to obtain reflection spectral polarization independence for any modulation depth with the proper parameters. The experimental behavior was confirmed by numerical simulations based on the Jones matrix formulation.